Echography of the Portal Vein in a Patient With Shock. Issue 6 (June 2016) - Piton, Gaël; Capellier, Gilles; Delabrousse, Eric
Abstract : Objectives: To report the utility of abdominal ultrasonography to identify portal venous gas in patients with shock, as an indicator of acute mesenteric ischemia, and to illustrate the aspect of portal venous gas on ultrasonography. Data Sources: Clinical observation of a patient, images of abdominal ultrasonography and abdominal computed tomography, and video of portal venous gas. Study Selection: Not applicable. Data Extraction: Relevant information contained in the medical observation of the patient and selection of image and video of ultrasonography performed in the patient. Data Synthesis: We report a case of nonocclusive mesenteric ischemia in a 76-year-old patient following cardiac surgery. The diagnosis of acute mesenteric ischemia was proposed based on evidence of portal venous gas on abdominal ultrasonography and then confirmed by abdominal computed tomography showing transverse colonic ischemia, the presence of gas in the mesenteric veins but not in the portal vein. Urgent laparotomy confirmed extensive nonocclusive mesenteric ischemia, and the patient rapidly died of multiple organ failure. Conclusions: Intensive care physicians should be aware of the ultrasound characteristics of portal venous gas. In patients with shock, in addition to cardiac and thoracic echography, investigation of portal venous gas using bedside ultrasonography may help the clinician to identify patients in whom acute mesenteric ischemia develops. Abstract : Supplemental Digital Content is available in the text.